Association between herbivore stress and glutathione S-transferase expression in Pinus brutia Ten. - Semiz, A; í‡elik-Turgut, G; Semiz, G; í–zgün, í–; Åžen, A (Cellular and Molecular Biology, 2016)
Plants have developed mechanisms to defend themselves against many factors including biotic stress such as herbivores and pathogens. Glutathione S-transferase (GST) is a glutathione-dependent detoxifying enzyme and plays critical roles in stress tolerance and detoxification metabolism in plants. Pinus brutia Ten. is a prominent native forest tree species in Turkey, due to both its economic and ecological assets. One of the problems faced by P. brutia afforestation sites is the attacks by pine processionary moth (Thaumetopoea wilkinsoni Tams.). In this study, we investigated the changes in activity and mRNA expression of GST in pine samples taken from both resistant and susceptible clones against T. wilkinsoni over a nine month period in a clonal seed orchard. It was found that the average cytosolic GST activities of trees in March and July were significantly higher than the values obtained in November. November was considered to be the control since trees were not under stress yet. In addition, RT-PCR results clearly showed that levels of GST transcripts in March and July samples were significantly higher as compared to the level seen in November. These findings strongly suggest that GST activity from P. brutia would be a valuable marker for exposure to herbivory stress.